Pengaruh Partisipasi Masyarakat, Transparansi dan Akuntabilitas dalam Pengelolaan Dana Program Pemberdayaan Masyarakat - Novie Astuti Setianingsih; Wiwiek Kusumaning Asmoro; Eti Putranti (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to examine and analyze the effect of community participation, transparency and accountability in managing funds for community empowerment programs in the city of Kediri. Management of Community Empowerment Program funds through Village Deliberations to determine priorities, planning, implementation, supervision, administration, reporting, accountability from the Neighborhood Association to the Kelurahan, from the Kelurahan to the Regional Government. The scope of the Kediri City Community Empowerment Program is in the economic field. Health, Social, Education, Infrastructure and Youth. This research is a quantitative research by distributing questionnaires. The population in this study were 3 sub-districts (Betet, Tinalan and Banaran). Questionnaires were distributed to the community, the Neighborhood Association (RT) and village officials as implementers of the Community Empowerment Program activities. This study shows the results that community participation, transparency and accountability have a significant positive effect on the management of Community Empowerment Program funds.